Формировaние aдaптивной обрaзовaтельной среды подготовки мaгистрaнтов. Мaгистрaнттaрды дaйындaудың білімдік бейімделу ортaсын қaлыптaстыру. (Journal of Educational Sciences, 2018)
Research activity is a product of learning and the result of the self-development of the master. The development is not so much «technological» as personal growth, holistic self-organization and synthesisof your activity and personal experience. In general, the turn of education to the person, increase of its role in the development of the state and society of knowledge, necessitates a change of approach to theobjectives, content, organizational structure of professional training. In this regard, the author offers a rationale for consideration of the creation of active adaptive learning environment. At the same time, thearticle actualize the need to adapt the educational environment to the individual mechanisms of learning, using different combinations of the structures of intellectual processes, methods and techniques oflogical thinking, providing interdisciplinary content and more. The author consistently reveals the essence of research activity of undergraduates in the conditions of reflexive and generative organizationof education, reveals the potential adaptive role functions of the student. Then in the final part provides the requirements to the learner and organization of the educational process aimed at ensuring masteryof the methodology of research activities.Key words: subject of research activities, adaptive situation, adaptive strategy, adaptive behavior.